Implementation issues in tuberculosis/HIV program collaboration and integration: 3 case studies. - Friedland, Gerald; Harries, Anthony; Coetzee, David (The Journal of infectious diseases, 2007)
The many interactions between tuberculosis (TB) and human immunodeficiency virus (HIV) infection influence the design and implementation of programs to address the needs of patients living with or at risk for both diseases. Collaboration between national TB and HIV programs and some degree of integration of services at a local level have been advocated by the World Health Organization and other international bodies and are recognized as essential in areas where the 2 diseases are prevalent. However, in most settings, strategies to accomplish this are only beginning to reach the field where their impact will be made and the expectation of improving the outcome of both diseases realized. In this article, 3 such strategies, offering varying degrees of collaboration and integration, are described, 1 at a national level in Malawi and 2 at local sites in South Africa. These geographically and programmatically distinct experiences in TB/HIV service integration are instructive, illustrate common themes, and show that the strategy can be successful, but they also show that programmatic, medical, staffing, resource, and scale-up challenges remain. In addition, they indicate that, although broad program principles of TB/HIV service integration are essential, program designs and components may vary by country and even within countries, as a result of differing TB and HIV disease prevalences, resources, levels of expertise, and differences in program settings (urban vs. rural and/or primary vs. district vs. specialty site). Large national programs can successfully provide rapid, uniform and widespread change and implementation but also must negotiate the subtleties of intricacies of TB/HIV interactions, which confound a uniform "one size fits all" public health approach. Conversely, smaller demonstration projects, even with successful outcomes, must grapple with issues related to generalization of findings, wider implementation, and scale up, to benefit larger populations of those in need.
Keywords: Adolescent; Adult; Anti-Retroviral Agents; Antitubercular Agents; Child; Cooperative Behavior; HIV; HIV Infections; Humans; Management Service Organizations; National Health Programs; Program Evaluation; Rural Population; South Africa; Treatment Outcome; Tuberculosis; Urban Population